Effects of deployment on diet quality and nutritional status markers of elite U.S. Army special operations forces soldiers - Emily K. Farina (Nutrition Journal, 2017)
Abstract Background Special Operations Forces (SOF) Soldiers deploy frequently and require high levels of physical and cognitive performance. Nutritional status is linked to cognitive and physical performance. Studies evaluating dietary intake and nutritional status in deployed environments are lacking. Therefore, this study assessed the effects of combat deployment on diet quality and serum concentrations of nutritional status markers, including iron, vitamin D, parathyroid hormone (PTH), glucose, and lipids, among elite United States (U.S.) Army SOF Soldiers. Methods Changes from baseline to post-deployment were determined with a repeated measure within-subjects design for Healthy Eating Index-2010 (HEI-2010) scores, intake of foods, food groups, key nutrients, and serum nutritional status markers. Dietary intake was assessed with a Block Food Frequency Questionnaire. The association between post-deployment serum 25-hydroxy vitamin D (25-OH vitamin D) and PTH was determined. Analyses of serum markers were completed on 50 participants and analyses of dietary intake were completed on 33 participants. Results In response to deployment, HEI-2010 scores decreased for total HEI-2010 (70.3 ± 9.1 vs. 62.9 ± 11.1), total fruit (4.4 ± 1.1 vs. 3.7 ± 1.5), whole fruit (4.6 ± 1.0 vs. 4.2 ± 1.4), dairy (6.2 ± 2.7 vs. 4.8 ± 2.4), and empty calories (14.3 ± 3.2 vs. 11.1 ± 4.5) (P ≤ 0.05). Average daily intakes of foods and food groups that decreased included total dairy (P < 0.01), milk (P < 0.01), and non-juice fruit (P = 0.03). Dietary intake of calcium (P = 0.05) and vitamin D (P = 0.03) decreased. PTH increased from baseline (3.4 ± 1.6 vs. 3.8 ± 1.4 pmol/L, P = 0.04), while there was no change in 25-OH vitamin D. Ferritin decreased (385 ± 173 vs. 354 ± 161 pmol/L, P = 0.03) and soluble transferrin receptor increased (16.3 ± 3.7 vs. 17.1 ± 3.5 nmol/L, P = 0.01). There were no changes in glucose or lipids. Post-deployment, serum 25-OH vitamin D was inversely associated with PTH (r = −0.43, P < 0.01). Conclusions HEI-2010 scores and dietary intake of milk, calcium, and vitamin D decreased following deployment. Serum PTH increased and iron stores were degraded. No Soldiers were iron deficient. Personnel that deploy frequently should maintain a high diet quality in the U.S. and while deployed by avoiding empty calories and consuming fruits, vegetables, and adequate sources of calcium, vitamin D, and iron. Improving availability and quality of perishable food during deployment may improve diet quality.